Collagen immunoassay as a method to optimise surface functionalisation. Issue 9 (7th February 2017) - Stynes, Gil; Kiroff, George; Morrison, Wayne; Kirkland, Mark
Abstract : Traditional methods of assessing surface functionalisation, including spectroscopy and chemical labelling, often involve significant error and conjecture about bonds. Proteins that improve cell attachment have specific pKa's and optimum binding requirements that may differ from the conditions required for chemical labelling. The utility of collagen ELISA to optimise acetaldehyde glow discharge polymerisation reactor parameters was tested. Accurate stepwise increases in collagen conjugation strength were demonstrated by incubating specimens in 8 M urea for 5–8 days followed by ELISA to test for residual surface collagen. Surface modifications also were assessed by XPS. The results indicated that ELISA after bond‐stressing with urea may suffice for optimising surface functionalisation and that traditional methods of analysis may be superfluous if protein conjugation is the aim of functionalisation. Abstract : Traditional methods of assessing surface functionalisation, including spectroscopy and chemical labelling, often involve significant error and conjecture about bonds. Proteins that improve cell attachment have specific pKa's and optimum binding requirements that may differ from the conditions required for chemical labelling. The utility of collagen ELISA to optimise acetaldehyde glow discharge polymerisation reactor parameters was tested. Accurate stepwise increases in collagen conjugation strength were demonstrated by incubating specimens in 8 M urea for 5–8 days followed by ELISA to test for residual surface collagen. Surface modifications also were assessed by XPS. The results indicated that ELISA after bond‐stressing with urea may suffice for optimising surface functionalisation and that traditional methods of analysis may be superfluous if protein conjugation is the aim of functionalisation.